Demand-side determinants of access to healthcare services: Empirical evidence from Africa - Wa Ntita Serge Kabongo; Josue Mbonigaba (SPOUDAI - Journal of Economics and Business, 2017)
The problem of low access to health care services in Africa remains challenging to policy makers whave thus far not sufficiently contemplated polices on the demand-side factors. To assist ipolicymaking, the present study identifies the key determinants of access to healthcare in Africa aestimates the short-run and long run effects of these determinants. Panel data from 37 Africacountries, collected from the World Bank Development Indicators for the period 1995-2012, aanalysed using the pooled mean group estimators. Income appears the strongest determinant of accein the long run in countries in Africa included in the sample. Access to healthcare was a necessiwith the long-run income elasticity for access to healthcare being 0.1149. The short-run effects oincome on access were, however, only significant in four of the countries in the sample. Tdifference in the effects of income in the short run and the long run was generally applicable to othvariables. These findings imply that policy makers should focus on income to increase access healthcare while taking cognisance of country-specific conditions in the short run to mitigate varyilevels of shocks.
Keywords: I11; I15; I18; C23; 330; access to healthcare; dynamic panel data; Africa